A New Pre-descemetic Corneal Ring (Neoring) in Deep Anterior Lamellar Keratoplasty for Moderate-Advanced Keratoconus: A Pilot 2-Year Long-Term Follow-Up Study - Alfonso-Bartolozzi, Belén; Lisa, Carlos; Fernández-Vega-Cueto, Luis; Madrid-Costa, David; Alfonso, José F. (Frontiers in Medicine, 2021)
Purpose: To assess the outcomes of implanting a new PMMA ring (Neoring; AJL Ophthalmic) in pre-Descemet DALK (PD-DALK) procedure for moderate-advanced keratoconus. Methods: This prospective study included 10 eyes of 10 patients with moderate-advanced keratoconus who underwent PD-DALK with Neoring implantation. Neoring was implanted in a pre-Descemetic pocket. Postoperative examination included refraction, corrected distance visual acuity (CDVA), corneal tomography, and endothelial cell density (ECD). The root mean square (RMS) for coma-like aberrations and spherical aberration was evaluated for a pupil size of 4.5 mm. The junctional graft (Tg) and host (Th) thickness was measured. The postoperative follow-up was 24 months. Results: Postoperative CDVA was 0.82 ± 0.14 (decimal scale), 100% of the eyes achieved a CDVA of 0.7 (decimal scale). The refractive cylinder was -2.86 ± 1.65 two-years after surgery. No eyes had a postoperative refractive cylinder ≥ 5.00D and in 5 eyes (50%) was ≤ 2.50D. At the last visit, the mean keratometry was 45.64 ± 1.96D, the RMS for coma-like aberrations was 0.30 ± 0.15 m, and spherical aberration 0.22 ± 0.09. The mean ECD remains without changes over the follow-up (P=0.07). At the last visit, Tg and Th were 679.9 ± 39.0 µm and 634.8 ± 41.2 µm, respectively. The thickness of the complex (host-Neoring) was 740.6 ± 35.6 µm. In all cases this thickness was thicker than Tg. Conclusion: The results of this study suggest that PD-DALK along Neoring implantation is a viable, effective and safe option to optimize the postoperative results for moderate-severe keratoconus.